2000
DOI: 10.1159/000016617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Apis mellifera</i> Propolis on the Activities of Streptococcal Glucosyltransferases in Solution and Adsorbed onto Saliva–Coated Hydroxyapatite

Abstract: Propolis, a resinous hive product collected by Apis mellifera bees, has been used for thousands of years in folk medicine. Ethanolic extracts of propolis (EEP) have been shown to inhibit the activity of a mixture of crude glucosyltransferase (Gtf) enzymes in solution. These enzymes synthesize glucans from sucrose, which are important for the formation of pathogenic dental plaque. In the present study, the effects of propolis from two different regions of Brazil on the activity of separate, purified Gtf enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 36 publications
4
82
0
5
Order By: Relevance
“…The results obtained in the present study identified some of the compounds that may have been responsible for the previously reported effects of propolis on GTFs and bacterial growth (28,29,30,40). In general, flavonoids were the most active compounds, displaying distinct biological properties; flavones and flavonols were effective GTF inhibitors, whereas flavanones and the dihydroflavonol pinobanksin-3-acetate showed antibacterial activity.…”
Section: Vol 46 2002 Biological Effects Of Propolis Compounds 1305supporting
confidence: 61%
See 2 more Smart Citations
“…The results obtained in the present study identified some of the compounds that may have been responsible for the previously reported effects of propolis on GTFs and bacterial growth (28,29,30,40). In general, flavonoids were the most active compounds, displaying distinct biological properties; flavones and flavonols were effective GTF inhibitors, whereas flavanones and the dihydroflavonol pinobanksin-3-acetate showed antibacterial activity.…”
Section: Vol 46 2002 Biological Effects Of Propolis Compounds 1305supporting
confidence: 61%
“…For surface assays, the GTFs were adsorbed to hydroxyapatite beads coated with clarified whole saliva (free of GTF activity) as detailed elsewhere (30,43,51). The sHA beads were exposed to sufficient enzyme to saturate the surface as determined experimentally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tal constatação confi rma que esse produto possui ação antimicrobiana contra os patógenos bucais (Ota & Valente, 1998;Pamplona, 1997 (Koo et al, 2000;Park et al1998;Ota & Valente, 1998).…”
Section: Discussionunclassified
“…Existem vários relatos atribuindo à própolis as mais variadas aplicações na medicina popular e, de fato, os estudos vêm corroborando que a própolis possui um grande potencial terapêutico, principalmente em relação às atividades antimicrobiana, antiinflamatória, cicatrizante, anestésica, antitripanossomal (GHISALBERTI, 1979;MAREKOV, 1989;KHAYYAL;ELGHAZALY;ELKHATIB, 1993;KUJUMGIEV et al, 1999;MARCUCCI et al, 2001;ALENCAR, 2002;MONTPIED et al, 2003, ALENCAR et al, 2007, anticariogênica (PARK et al 1998a;PARK et al, 1998b;KOO et al, 1999;KOO et al, 2000a;KOO et al, 2000b;ROSALEN et al, 2002;MURATA et al, 2003;DUARTE et al, 2003;HAYACIBARA et al, 2005;CASTRO et al, 2007), antiviral, anticarcinogênica, antioxidante (BURDOCK, 1998MARCUCCI, 1996;CHEN et al, 1996;BANKSOTA et al, 2000;ALENCAR, 2002;CHEN et al, 2003;NAGAI et al, 2003;ASO et al, 2004;ISHIKAWA et al, 2004;NAKAYAMA, 2004;OLDONI, 2007) e fitotóxica (GHISALBERTI, 1979;JOHNSON;EISCHEN;GIANASSI, 1994).…”
Section: Propriedades Biológicas Da Própolisunclassified